2018
DOI: 10.1097/md.0000000000012475
|View full text |Cite
|
Sign up to set email alerts
|

Metal allergy in total-joint arthroplasty

Abstract: Rationale:Due to the low incidence and lack of effective diagnostic measures for the diagnosis of metal allergy in patients undergoing total joint arthroplasty (TJA), diagnosis relies mainly on the exclusion of other causes, in particular infection. It remains a relatively unpredictable and poorly understood cause of implant failure. At present, skin patch testing, leukocyte migration inhibition test (LMIT) and lymphocyte transformation tests (LTT) are being commonly used to assess metal hypersensitivity.This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
12
0
4
Order By: Relevance
“…The results of this study are in agreement with several case reports in the literature Caicedo et al demonstrated a significant percentage of patients that had undergone total joint arthroplasty and had unexplained joint pain were hypersensitive to implant metals [24]. Bao et al presented a case report in which a patient with continuous swelling of their total knee arthroplasty showed significant improvement after a synovectomy and component revision [25]. Overall, in the absence of obvious etiology, patients presenting with pain, decreased range of motion, and even contact dermatitis-like reactions have resolution of their symptoms after revision to a hypoallergenic component.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are in agreement with several case reports in the literature Caicedo et al demonstrated a significant percentage of patients that had undergone total joint arthroplasty and had unexplained joint pain were hypersensitive to implant metals [24]. Bao et al presented a case report in which a patient with continuous swelling of their total knee arthroplasty showed significant improvement after a synovectomy and component revision [25]. Overall, in the absence of obvious etiology, patients presenting with pain, decreased range of motion, and even contact dermatitis-like reactions have resolution of their symptoms after revision to a hypoallergenic component.…”
Section: Discussionsupporting
confidence: 90%
“…A high prevalence of contact allergies to metals exists with up to 24.4% to nickel, 8.8% to cobalt, 5.9% to chromium, and 0.2% to 3% to Titanium. 10 , 11 It is thought that jewelry is the most common cause of exposure, but patients can be exposed to metal in various ways. 12 This can occur through the skin in the form of cell-phones, clothing fasteners, and leather.…”
Section: Potential Causesmentioning
confidence: 99%
“…In particular, atopic dermatitis concerns 15% to 20% of adults in Northern Europe. The prevalence of cutaneous metal hypersensitivity in the population is between 10% and 15% in descending order: nickel, cobalt, and chromium2,3). This prevalence could increase to 25% for patients with a metal implant with a good functional result and to 60% for those with a poor functional result2,4).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of cutaneous metal hypersensitivity in the population is between 10% and 15% in descending order: nickel, cobalt, and chromium2,3). This prevalence could increase to 25% for patients with a metal implant with a good functional result and to 60% for those with a poor functional result2,4). The concept of hypersensitivity to metallic orthopedic implants was introduced in the late 90s3) and can cause pain, aseptic loosening and synovial reactions even though the link between symptoms and allergy remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation